Terrible choices in the septic child: a response to the PALOH trial round table authors - Parker, Joshua (Journal of medical ethics, 2021)
In this response article, we challenge a core assumption that lies at the centre of a round table discussion regarding the Pharmacogenetics to Avoid Loss of Hearing trial. The round table regards a genetic test for a variant (mt.1555A>G) that increases the risk of deafness if a carrier is given the antibiotic gentamicin. The idea is that rapid testing can identify neonates at risk, providing an opportunity to prevent giving an antibiotic that might cause deafness. We challenge the assumption that a positive test unequivocally guides antibiotic choice because, aside from the risk of deafness, all antibiotics for neonatal sepsis are equivalent. We argue that this assumption is faulty and has particularly troubling moral consequences. We claim that giving an alternative to gentamicin is potentially providing inferior treatment and thereby may increase the risk of death. Parents and doctors are faced with a terrible choice as a result of positive point-of-care testing (POCT): give gold-standard treatment and risk deafness or give second line care and risk death. While we do not indicate an answer to this choice, what we do argue is that such a deep and difficult choice is one that may make parents wish genetic testing was never undertaken, and therefore, contra some authors in the round table, provides a reason to gain specific consent for POCT.